Evaluation of atomization characteristics of second generation biodiesel using air blast atomizer - Muthaiyah G. (Science Publishing Corporation Inc, 2023)
Biodiesel is one of the well-known renewable fuels that can be produced from organic oils and animal fats. Biodiesel fuel that meets ASTM D6751 fuel standards can replace diesel for reciprocating engine. On the other hand, biodiesel can also be considered for gas turbine application in power generation. Nevertheless, inferior properties of biodiesel such as high viscosity, density and surface tension results in inferior atomization and high emission which consequently hinders the fuel for gas turbine utilisation and generate higher emission pollutants. Therefore, this work focused on the evaluation of atomization characteristics of second generation biodiesel which is produced using microwave assisted post treatment scheme. The atomisation characteristics of second generation biodiesel was evaluated using air blast atomiser in terms of spray angle and spray length. Subsequently, numerical evaluation was performed to evaluate sauter mean diameter and droplet evaporation time of second generation biodiesel. The results show, atomization characteristics of second generation biodiesel has improved in terms of spray angle and spray length, sauter mean diameter and shorter evaporation time compared to biodiesel which is commonly referred to as first generation biodiesel and fossil diesel. 2018 Authors.